The triangular relationship between Beijing, Washington and Taipei: strategies of intergovernmental organizations since 1949 - Ma, Jinpeng (2023)
The aim of this thesis is to investigate the triangular Beijing–Washington–Taipei relationship through their performance in intergovernmental organizations (IGOs) and the strategies they have employed in IGOs since 1949 through empirical case studies of the United Nations, the World Trade Organization, and the World Health Organization. These three case studies are analysed based on chronological order, and they represent the triangular relationship in different fields, including politics, economics, and public health. In IGO studies, neoliberal institutional scholars usually regard IGOs as the product and platform of cooperation among countries. Realists regard IGOs as a tool for global superpowers to maintain their hegemony. Through documentary analysis of the motivation and position taking of the three political actors in the case studies, it is found that IGOs also function as leverage in the triangular relationship and help political actors to implement their policies. Many previous studies of this triangular relationship have largely relied on the perspectives of either realism, which is characterized by national interests and power distribution, or liberalism, which is characterized by cooperation and interdependency but which disregards the roles of values and identity. By evaluating the multilayered factors in the three case studies in different historical scenarios, it is also found that constructivist factors can work when realistic factors play a fundamental role in the triangular IGO competition. This thesis thus constructs a compound theoretical framework that provides a comprehensive historical view of the dynamics of the triangular IGO competition. In addition, elite interviews serve as a supplementary method of data collection. The interviews provide more updated and diversified academic ideas to complete the thesis and inspire further discussions of the triangular relationship, as well as of the role of IGOs in future international order and relations.